Empowering Nursing Students to Adopt and Embody Strengths-Based Nursing and Healthcare. - Lapierre, Judith; Bernardino, Elizabeth; Encarnação, Paula; Bouchlaghem, Amine Mohamed; Rorato, Camilla (Nursing Leadership (1910-622X), 2024)
This paper presents an international academic partnership in teaching and research with two case studies. The cases explore the integration of Strengths-Based Nursing and Healthcare (SBNH) and SBNH-Leadership (SBNH-L) in nursing science programs. SBNH values and foundations were integrated within an undergraduate-level community health course in Canada and SBNH-L was introduced into a graduate-level program in Brazil. Both cases comprise active learning activities promoting the uptake of the values and foundations of SBNH and the capacity to identify strengths and innate capacities. This paper synthesizes the issues and provides recommendations to enhance teaching-learning strategies to support SBNH adoption by students to support the humanization of healthcare. International partnerships in education and research and facilitating factors are discussed.